Trust framework for online products and services using grain level comparison: A solution to boot-strapping problem. Issue 1 (December 2020) - Talib, M N; Akhtar, M; Jhanjhi, NZ; Suseendran, G.
Abstract: Service-oriented architecture has changed the way that web applications are designed. Today users are more inclined towards online products and services to save time, energy, and cost. However existing frameworks for online purchasing have certain drawbacks and one of the foremost is 'trust'. Hence the struggle is to build such a system trust that offers commendations to the customer for the products and services even with inadequate resources; consequently building customer's trust upon the vender as well as the system. Current systems available only utilize trust by providing product features and comparison using the rating system. However, a problem occurs when a "Bootstrapping issue" is raised, i.e., if a new company emerges in the market then the existing system cannot generate a trust rating for it; the same goes for the new product. Such a problem can cause an uncertain situation for the customer to; a) whether go for the existing product or b) the new product of a new company. In this article, we propose a system trust using a novel framework, which can solve the problem of bootstrapping using a 'grain level approach'. By providing a high level of granularity, the details of the product's specs and features will be much in-depth, which will offer the customer an enhanced platform to examine and compare the product amongst several other similar products and ultimately coming to a decision to purchase it by trusting it. As a result, the decision-making power of the customers will be strengthened and the system's trust will be extended.